Determining the Factors for Analytical Competencies in Mitigating Employees Resilience: An Empirical Examination - KishanVarma, M S; Kalpana, Dr K (The journal of contemporary issues in business and government, 2021)
The purpose of the study is to know the employees perception about analytical competencies. In order to get employment opportunities’ in the recent corporate world it was important to be updated with better skills and knowledge, which will help the employees to get better employment opportunities in the growing job market. However, we have attempted to know the student perception about their opinion over the statement and how they think it will help them to grow in their career for better employment opportunities. We also attempted to know that what they think about the best way to enhance their analytical competencies. We have done this through focused group interviews with the employees to explore the difference between the academics and the practical reality and their opinions and suggestions over the employability to cope up with the reality. From this study we find that there is a need of a better communication about the various skills and technological improvements which can help them to enhance their analytical competencies.